Risk and risk assessment - Middle, Gary (2017)
© 2018 Taylor & Francis. This chapter covers the broad notions of risk and risk assessment, and how they are applied within the practice of Environmental and Social Impact Assessment (ESIA). It starts with a brief history of risk assessment followed by a discussion of quantitative risk assessment. The limitations and criticism of quantitative risk assessment are then discussed, leading into an examination of qualitative risk assessment. The chapter finishes with a discussion of risk in a broader context and its relevance to ESIA.